A new concept to design combined support under dynamic loading using numerical modelling. (November 2021) - Tahmasebinia, Faham; Zhang, Chengguo; Wei, Chunchen; Canbulat, Ismet; Saydam, Serkan; Sepasgozar, Samad
Highlights: Assessed the energy absorption capacity of several ground support elements. Determined the interaction relationships between the support elements. Proposed a design concept for combined support under dynamic loading. Abstract: A rock and/or coal burst is an uncontrolled failure that releases a massive amount of kinetic energy, inducing excessive displacement of coal/rock mass. Combined support to controlling rock and/or coal dynamic failures is an essential part of the rock burst management. In the design of rock support, it is essential to consider not only the capacity of the individual elements but also their compatibility with each other and their interactions. This paper aimed to develop a novel full-scale numerical procedure to evaluate the behaviour of individual support elements and their interactions under dynamic loads using Finite Element Commercial Package ABAQUS/Explicit. A mutual interaction relationship between two indicators, namely Cable/Rock Bolt Dissipated Energy and the Steel Mesh Dissipated Energy is also developed, and an interaction diagram is provided. The proposed design concept can be used for the selection of an appropriate support system for coal burst management.